Pengaruh Kualitas Produk, Kualitas Pelayanan, Lokasi dan Persepsi Harga Terhadap Keputusan Pembelian - Rahma, Aisyah Fadila; Moeljono, Moeljono (IJMA (Indonesian Journal of Management and Accounting), 2023)
This study aims to examine the analysis of the effect of product quality, service quality, location, and price perceptions on purchasing decisions at Bang Oye food stalls in Semarang. Some previous research on purchasing decisions shows different results. Therefore, this study aims to review previous research on purchasing decisions. This study used a sample of 97 respondents of Bang Oye food stall consumers. The sampling method is the Snowball Sampling method. The method of analysis of this research is Multiple Linear Regression Analysis using the SPSS Version 25.0 analysis tool. The results of the study indicate that the three variables, namely Product Quality, Service Quality, and Location, have no positive and significant effect on Purchasing Decisions. However, the Price Perception variable has a positive and significant effect on purchasing decisions.